Mollusca of the family Mytilidae (Bivalvia) associated with organic remains from deep water off New Zealand, with revisions of the genera Adipicola Dautzenberg, 1927 and Idasola Iredale, 1915 - Dell, R. K. (National Museum of New Zealand Records 3 (3): 17-36, 1987)
Collections of small mytilid bivalves from sunken wood and other organic remains from deep water off New Zealand represent four species belonging to three genera. A critical review of the relevant genera shows that the species concerned should be grouped in Adipicola Dautzenberg, 1927 (= Myrina H. & A. Adams, 1857 = Terua Dali, Bartsch & Rehder, 1938), Idasola Iredale, 1915 (= Idas Jeffreys, 1876 = Miridas Iredale, 1939 = Myrinopsis Nordsieck, 1969 = Habepegris Bernard, 1978), and in a new genus, Benthomodiolus, erected for Modiolus abyssicola Knudsen, 1970 from the Gulf of Panama and B. lignocola n.sp. from New Zealand. A new species Adipicola osseocola is described from New Zealand, whilst Idasola washingtoniana (Bernard), originally described from the North Pacific, is recorded from Japan and New Zealand, and I. japonica, described from off Japan, is also recorded from New Zealand waters. The species pelagica Woodward, 1854, crypta Dali, Bartsch & Rehder, 1938, iwaotakii Habe, 1958, longissima Thiele & Jaeckel, 1932, pacifica Dali, Bartsch & Rehder, 1938 and simpsoni Marshall, 1900 are considered to belong to Adipicola, with argenteus Jeffreys, 1876, coppingeri Smith, 1885, modiolaeformis Sturany, 1896, indica Smith, 1904, japonica Habe, 1976 and washingtoniana Bernard, 1979 in the genus Idasola.